Identifying Google Translation And Students’ Vocabulary Mastery In Suburban Senior High School - Muhammad Yusril Setya Nugraha; Yeni Rahmawati (Departement of Mathematics Education, 2024)
One of the most essential human needs is language since it serves as a means of communication between people. Google Translation provides a general definition of words; hence, learners who use it may have varied interpretations of the meaning of the word. The development of proficiency and attainment of competency in the target language are largely dependent on vocabulary learning. most learners in Indonesia speak English under specific conditions. Based on the previous studies the first time they collected the data; it was shown that under 50% of students have been involved in application or other media to learn English. This essay employs a mixed-method approach that combines quantitative and quantitative techniques. The first question will be analyzed using a qualitative method to determine the suburban school kids' motivation. A quantitative approach would be used to analyze the second question. Senior high school students would make up the study's population. The observation states that a suburb is usually located outside of a city or town and has a lower population density than an urban area. the researcher decided to use SMA Negeri 15 Samarinda to conduct the study. This school is built in a suburban area which is far from the city but internet access still exists. The total population of this research was 140 students from grades 10 to 11. Therefore, the researcher employed simple random sampling techniques to take a sample. Based on the data analysis, it was found that the majority of the students used Google Translate for every activity they needed.